Long-term efficacy of microwave ablation in the treatment of subcapsular hepatocellular carcinomas of ≤3 cm in diameter: a multicenter, propensity score-matched study. (31st December 2022) - Yao, Jundong; Liu, Binbin; Wang, Xiaohui; Yu, Jie; Cheng, Zhigang; Han, Zhiyu; Liu, Fangyi; Zheng, Rongqin; Cheng, Wen; Wei, Qiang; Yu, Songyuan; Li, Kai; et al.
Abstract: Objective: To compare the long-term efficacy of microwave ablation (MWA) for subcapsular and non-subcapsular hepatocellular carcinomas (HCCs) using propensity score matching (PSM). Materials and methods: Using a multicenter database, we enrolled 430 patients (347 men, 83 women; age range, 15–71 years) with HCCs who received percutaneous ultrasound-guided MWA, between January 2012 and December 2018. The patients were grouped as follows, based on whether the tumor was adjacent to the capsule: subcapsular group ( n = 142) and non-subcapsular group ( n = 142). To evaluate the correlation between subcapsular position and efficacy of MWA, a Cox proportional hazards model was used to calculate disease-free survival (DFS) and overall survival (OS) based on PSM data. Results: In total, 142 pairs of patients were matched. In the PSM cohort, the 1-year, 3-year, and 5-year DFS rates of the subcapsular and non-subcapsular groups were 84%, 61%, and 47%, respectively, and 85%, 67%, and 58%, respectively, while the 1-year, 3-year, and 5-year OS rates were 98%, 90%, and 84%, respectively, and 98%, 90%, and 88%, respectively. In the PSM cohort, subcapsular position was not an independent risk factor for DFS (hazard ratio [HR] = 1.291, p = 0.196) or OS (HR = 0.926, p = 0.866). Additionally, there were no significant differences in the incidence of local tumor progression, major complications, technical success rate, number of puncture needles, and postoperative hospital stay between the two groups ( p > 0.05). Conclusion: There were no significant differences in DFS, OS, incidence of local tumor progression, and major complications between patients with subcapsular and non-subcapsular HCCs treated with MWA.